The immune suppressive properties of damage associated molecular patterns in the setting of sterile traumatic injury - Horner, Emily; Lord, Janet M.; Hazeldine, Jon (Frontiers in Immunology, 2023)
Associated with the development of hospital-acquired infections, major traumatic injury results in an immediate and persistent state of systemic immunosuppression, yet the underlying mechanisms are poorly understood.Detected in the circulation in the minutes, days and weeks following injury, damage associated molecular patterns (DAMPs) are a heterogeneous collection of proteins, lipids and DNA renowned for initiating the systemic inflammatory response syndrome. Suggesting additional immunomodulatory roles in the post-trauma immune response, data are emerging implicating DAMPs as potential mediators of post-trauma immune suppression.Discussing the results of in vitro, in vivo and ex vivo studies, the purpose of this review is to summarise the emerging immune tolerising properties of cytosolic, nuclear and mitochondrial-derived DAMPs. Direct inhibition of neutrophil antimicrobial activities, the induction of endotoxin tolerance in monocytes and macrophages, and the recruitment, activation and expansion of myeloid derived suppressor cells and regulatory T cells are examples of some of the immune suppressive properties assigned to DAMPs so far. Crucially, with studies identifying the molecular mechanisms by which DAMPs promote immune suppression, therapeutic strategies that prevent and/or reverse DAMP-induced immunosuppression have been proposed. Approaches currently under consideration include the use of synthetic polymers, or the delivery of plasma proteins, to scavenge circulating DAMPs, or to treat critically-injured patients with antagonists of DAMP receptors. However, as DAMPs share signalling pathways with pathogen associated molecular patterns, and pro-inflammatory responses are essential for tissue regeneration, these approaches need to be carefully considered in order to ensure that modulating DAMP levels and/or their interaction with immune cells does not negatively impact upon anti-microbial defence and the physiological responses of tissue repair and wound healing.